2016
DOI: 10.1371/journal.pone.0168719
|View full text |Cite
|
Sign up to set email alerts
|

System-Wide Adaptations of Desulfovibrio alaskensis G20 to Phosphate-Limited Conditions

Abstract: The prevalence of lipids devoid of phosphorus suggests that the availability of phosphorus limits microbial growth and activity in many anoxic, stratified environments. To better understand the response of anaerobic bacteria to phosphate limitation and starvation, this study combines microscopic and lipid analyses with the measurements of fitness of pooled barcoded transposon mutants of the model sulfate reducing bacterium Desulfovibrio alaskensis G20. Phosphate-limited G20 has lower growth rates and replaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 83 publications
2
24
0
Order By: Relevance
“…Morphological changes observed in the two Desulfovibrio spp. we tested (see below), as well as structural adaptations to phosphate limitation and starvation observed in D. desulfuricans (Weimer et al, 1988) and D. alaskensis G20 (Bosak et al, 2016) are consistent with the higher bulk C:P ratio in phosphate-limited D. desulfuricans (Okabe and Characklis, 1992). …”
Section: Discussionsupporting
confidence: 67%
“…Morphological changes observed in the two Desulfovibrio spp. we tested (see below), as well as structural adaptations to phosphate limitation and starvation observed in D. desulfuricans (Weimer et al, 1988) and D. alaskensis G20 (Bosak et al, 2016) are consistent with the higher bulk C:P ratio in phosphate-limited D. desulfuricans (Okabe and Characklis, 1992). …”
Section: Discussionsupporting
confidence: 67%
“…Figure 3 shows changes in the relative abundances (as percentages of total IPLs, excluding isoprenoidal archaeal IPLs) of glycolipids, phospholipids and aminolipids as well as several substitute lipid ratios, reflecting the preferential biosynthesis of non-phosphorus lipids to replace phospholipids under phosphate-limiting growth (cf. Van Mooy et al, 2006;Popendorf et al, 2011b;Carini et al, 2015;Bosak et al, 2016). Relative abundances of non-isoprenoidal phospholipids were highest in the core OMZ between 400 and 600 m at all sites, where they comprise up to 45 %-76 % at Stations 1, 2 and 5 and between 12 % and 61 % at Station 8.…”
Section: Changes In Ipl Composition With Water Column Depth In the Etnpmentioning
confidence: 91%
“…The assignment of the betaine lipid DGTS was according to the retention time of the commercially available standard DGTS (Avanti Polar Lipids, USA). The isomer DGTA, which elutes at a different retention time due to its structural difference (e.g., Brandsma et al, 2012), was not observed in the HPLC-MS chromatograms. For all analyses, response factors of individual IPLs relative to the injection standard C 19 -PC were determined using dilution series of commercially available standards (Table S2).…”
Section: Lipid Extraction and Analysis Of Intact Polar Lipidsmentioning
confidence: 94%
See 2 more Smart Citations